Effect of Reflexology Therapy On Decreased Intensity of Menstrual Pain - Nur Afni; Tenriwati; Haerati (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2021)
Pharmacological treatment of menstrual pain relief and non-pharmacological treatment such as reflexology, reflexology massage can be done on the feet and hands so that these points provide a spontaneous relaxation stimulation when massaged so that pain is not felt. Purpose The purpose of this study was to determine the effect of giving reflexology therapy on reducing the intensity of menstrual pain in undergraduate nursing study program students at Panrita Husada College of Health Sciences, Bulukumba. Methods This study used a pre-experimental design with a one-group pretest-posttest design approach. The sample of this study was 41 respondents who were taken using the non-probability sampling method with the consecutive sampling technique. The experimental group received reflexology therapy once with a duration of 20 minutes. Analysis of the data in this study using the Wilcoxon test statistic. The results of the analysis used the Wilcoxon test statistical test with a level of confidence (Î± = 0.05). Based on the results of this test, the value of Ï = 0,000 was obtained, thus Ï <Î± (0,000 <0.05), so there was an effect of giving reflexology therapy on reducing the intensity of menstrual pain in undergraduate nursing study program students at Stikes Panrita Husada Bulukumba. The conclusion of this study is a Researchers suggest that the results of this study can provide information for people in the surrounding environment, families, and young women about how to deal with menstrual pain without consuming pharmacological drugs but in a non-pharmacological way, namely by using reflexology techniques.